New corticioid taxa in Phanerochaetaceae (Polyporales, Basidiomycota) from East Asia - Li, Yue; Chen, Che-Chih; He, Shuang-Hui (Frontiers in Microbiology, 2023)
The species diversity, taxonomy, and phylogeny of five corticioid genera of Phanerochaetaceae, namely, Hyphodermella, Roseograndinia, Phlebiopsis, Rhizochaete, and Phanerochaete, in East Asia are studied by using the morphological and molecular methods. Phylogenetic analyses were performed separately for the Donkia, Phlebiopsis, Rhizochaete, and Phanerochaete clades based on ITS1-5.8S-ITS2 and nrLSU sequence data. In total, seven new species were found, two new combinations are suggested, and a new name is proposed. In the Donkia clade, Hyphodermella sensu stricto was strongly supported with two new lineages, namely H. laevigata and H. tropica, which were recovered. Hyphodermella aurantiaca and H. zixishanensis are members of Roseograndinia, while R. jilinensis is proved to be a later synonym of H. aurantiaca. In the Phlebiopsis clade, P. cana sp. nov. was found on the bamboo from tropical Asia. In the Rhizochaete clade, four new species, R. nakasoneae, R. subradicata, R. terrestris, and R. yunnanensis were recovered based mainly on molecular analyses. In the Phanerochaete clade, P. subsanguinea nom. nov. is proposed to replace Phanerochaete rhizomorpha C.L. Zhao & D.Q. Wang, which is an invalid name because it was published after Phanerochaete rhizomorpha C.C. Chen, Sheng H. Wu & S.H. He, representing another species. Descriptions and illustrations are provided for the new species, and discussions are given for new taxa and names. Identification keys to Hyphodermella species worldwide and Rhizochaete species in China are given separately.